Congenital Myasthenic Syndrome: Spectrum of Mutations in an Indian Cohort. Issue 1 (September 2018) - Selvam, Pavalan; Arunachal, Gautham; Danda, Sumita; Chapla, Aaron; Sivadasan, Ajith; Alexander, Mathew; Thomas, Maya Mary; Thomas, Nihal J.
Abstract : Objectives: To investigate the mutational spectrum and genotype–phenotype correlation in Indian patients with congenital myasthenic syndrome (CMS), using next-generation sequencing of 5 genes. Methods: CHRNE, COLQ, DOK7, RAPSN, and GFPT1 were sequenced in 25 affected patients. Results: We found clinically significant variants in 18 patients, of which variants in CHRNE were the most common, and 9 were novel. A common pathogenic COLQ variant was also detected in 4 patients with isolated limb-girdle congenital myasthenia. Conclusions: Targeted screening of 5 genes is an effective alternate test for CMS, and an affordable one even in a developing country such as India. In addition, we recommend that patients with isolated limb-girdle congenital myasthenia be screened initially for the common COLQ pathogenic variant. This study throws the first light on the genetic landscape of CMSs in India.